An Analysis of Feeling Love and Hate in Sylvia Plath’s Poem “Daddy” - Herman Herman; Danul Aristiawan; Ria Hendriani (Journal of Languages and Language Teaching, 2020)
Sylvia Plath's poem "Daddy" remains one of the most controversial modern poems ever written. The aim of this research was to find the expresses of the aouthor feeling in the poem. The method used in this research was qualitative method with narrative approach. It showed the contradictory feelings between love as well as great hatred and disappoints feelings to her beloved daddy who does not gave any affection to her as a biological daughter. The author begins with her present understanding of her father and the kind of man that he was. As Daddy progresses, the readers begins to realize that the author has not always hated her father. She has not always seen him as a brute, although she makes it clear that he always has been oppressive. The author did not know anything apart from her father’s mentality, and so she prays for his recovery and then mourns his death. She even wishes to join him in death. The love came from Plath seeing her father as God when she was a child and from an obsessive need on the Plath’s part to love and to be loved. Meanwhile, the hate came from an intense, deep-rooted fear she felt towards her father, who completely dominated her life, viewing her unresolved feelings for her father as the root of all her pain and suffering. Plath uses various images to describe how she viewed her father. The images she uses change throughout the poem, causing the attitudes she communicates about her father to be inconsistent.